Título Padrão: Planktonic centric diatoms (Coscinodiscophyceae and Mediophyceae) from two tropical Brazilian estuaries: floristic survey and new records - do Nascimento Moura, Ariadne; Silva Diniz, Anamaria; Alves Amorim, Cihelio; Osman Ferreira de Brito, Jhullyrson; Ribeiro da Anunciação, Raylane; Lima do Nascimento Filho, Silvano; Arantes Gama, Watson (Arquivos de Ciências do Mar, 2022)
Estuaries are highly productive and dynamic ecosystems in which phytoplankton is the main primary producer and centric diatoms are the most abundant group seen in marine and estuarine phytoplankton. In this context, the aim of this study was to carry out a taxonomic study of the planktonic centric diatoms (Coscinodiscophyceae and Mediophyceae) from two tropical estuaries located in Northeast Brazil. This study was carried out before the biggest oil spill impact occurred in Brazil in 2019. Thirty-six taxa were identified, with Mediophyceae as the most representative class with 24 species. Coscinodiscus was the genus with the highest number of species identified, followed by Chaetoceros and Thalassiosira. The species Chaetoceros filiferus Karsten was reported for the first time to Brazil, while Paralia fenestrata Sawai & Nagumo and Shionodiscus endoseriatus (Hasle & Fryxell) Alverson are new records for Northeast Brazil and Thalassiosira lineata Jousé for Pernambuco state. Descriptions, illustrations, and comments on morphological and metric variations for each taxon were presented. The results highlight the importance of floristic studies for the knowledge of diatom flora in tropical marine environments, besides acting as a crucial study for future research in the studied estuaries. Keywords: Brazil, marine diatoms, phytoplankton, scanning electron microscopy, taxonomy